AN ALGORITHM INDEX MULTIMEDIA DATA (VIDEO) USING THE MOVEMENT ORIENTED METHOD FOR REAL-TIME ONLINE SERVICES - Muslim, Aries; Karyati, Cut Maisyarah (Jurnal Ilmiah Informatika Komputer, 2009)
Multimedia data is a form of data that can represent all types of data (images, sound and text). The use of multimedia data for the online application requires a more comprehensive database in the use of storage media, Sorting / indexing, search and system / data searching. This is necessary in order to help providers and users to access multimedia data online. Systems that use of the index image as a reference requires storage media so that the rules and require special expertise to obtain the desired file. Changes in multimedia data into a series of stories / storyboard in the form of a text will help reduce the consumption of media storage, system index / sorting and search applications. Oriented Movement is one method that is being developed to change the form of multimedia data into a storyboard.Keyword(s): Algorithm, Index, multimedia data, Movement Oriented.Subject description: H.2.Database Management | H.2.4.Systems \ Multimedia Databases